Penerapan Strategi 4C Dalam Membangun Brand Positioning Aneka 57 Melalui Media Sosial Instagram (Studi Kasus di Aneka 57 Melalui Akun Instagram @aneka57) - Pasha, Indhira Aprizka; Sugiana, Dadang; W, Teddy Kurnia (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze the implementation of the 4C marketing communication strategy (Co-creation, Currency, Communal Activation, and Conversation) carried out by Aneka 57. The decline in public interest in culinary tourism in Pecenongan occurs due to several factors, including the lack of variety in the food products offered, and lack of innovation following the latest trends that continue to develop. This research was conducted using a case study method with a qualitative approach. There is also research data obtained using interviews with 3 internal sources who are owners of Aneka 57, and 2 external sources who are consumers of Aneka 57. The results of the research that has been carried out show that the implementation of 4C marketing communications carried out by Aneka 57 via Instagram is considered quite effective in building the brand positioning to consumers. Threats originating from external factors do not cause concern for Aneka 57; on the contrary, this encourages Aneka 57 to continue to improve the quality of its services and products. Apart from that, there have been significant changes since Aneka 57 first opened and created an Instagram account.